Question (1i)
"z=\\sqrt{2x+a}+\\sqrt{2y+b}\\longrightarrow\\\\[0.3cm]\np=\\frac{\\partial z}{\\partial x}=\\frac{2}{2\\sqrt{2x+a}}\\equiv\\frac{1}{\\sqrt{2x+a}}\\\\[0.3cm]\nq=\\frac{\\partial z}{\\partial y}=\\frac{2}{2\\sqrt{2y+b}}\\equiv\\frac{1}{\\sqrt{2y+b}}\\\\[0.3cm]"
Then,
"\\frac{1}{p}+\\frac{1}{q}=\\frac{1}{\\frac{1}{\\sqrt{2x+a}}}+\\frac{1}{\\frac{1}{\\sqrt{2y+b}}}\\longrightarrow\\\\[0.3cm]\n\\frac{1}{p}+\\frac{1}{q}=\\sqrt{2x+a}+\\sqrt{2y+b}\\equiv z\\longrightarrow\\\\[0.3cm]\n\\boxed{z=\\sqrt{2x+a}+\\sqrt{2y+b}\\longrightarrow z=\\frac{1}{p}+\\frac{1}{q}}"
Question (ii)
"z^2+\\mu=2\\left(1+\\lambda^{-1}\\right)\\left(x+\\lambda y\\right)\\longrightarrow\\\\[0.3cm]\n2z\\cdot\\frac{\\partial z}{\\partial x}=2\\left(1+\\lambda^{-1}\\right)\\rightarrow p=\\frac{1+\\lambda^{-1}}{z}\\\\[0.3cm]\n2z\\cdot\\frac{\\partial z}{\\partial y}=2\\lambda\\left(1+\\lambda^{-1}\\right)\\rightarrow q=\\frac{\\lambda\\left(1+\\lambda^{-1}\\right)}{z}\\\\[0.3cm]"
Then,
"\\frac{1}{p}+\\frac{1}{q}=\\frac{1}{\\frac{1+\\lambda^{-1}}{z}}+\\frac{1}{\\frac{\\lambda\\left(1+\\lambda^{-1}\\right)}{z}}\\longrightarrow\\\\[0.3cm]\n\\frac{1}{p}+\\frac{1}{q}=\\frac{z}{1+\\lambda^{-1}}+\\frac{z}{\\lambda\\left(1+\\lambda^{-1}\\right)}\\longrightarrow\\\\[0.3cm]\n\\frac{1}{p}+\\frac{1}{q}=\\frac{z}{1+\\frac{1}{\\lambda}}+\\frac{z}{\\lambda+1}\\longrightarrow\\\\[0.3cm]\n\\frac{1}{p}+\\frac{1}{q}=\\frac{z\\lambda}{\\lambda+1}+\\frac{z}{\\lambda+1}\\longrightarrow\\\\[0.3cm]\n\\frac{1}{p}+\\frac{1}{q}=\\frac{z\\left(\\lambda+1\\right)}{\\lambda+1}\\equiv z\\\\[0.3cm]\n\\boxed{z^2+\\mu=2\\left(1+\\lambda^{-1}\\right)\\left(x+\\lambda y\\right)\\longrightarrow z=\\frac{1}{p}+\\frac{1}{q}}"
Question 2
Let suppose that "b=b(a;\\lambda,\\mu)" . Then,
"F(x,y,z,a,b)=\\sqrt{2x+a}+\\sqrt{2y+b}-z=0\\longrightarrow\\\\[0.3cm]\n\\frac{\\partial F}{\\partial a}=\\frac{1}{2\\sqrt{2x+a}}+\\frac{1}{2\\sqrt{2y+b}}\\cdot\\frac{db}{da}=0\\longrightarrow\\\\[0.3cm]\n\\frac{1}{2\\sqrt{2x+a}}=-\\frac{1}{2\\sqrt{2y+b}}\\cdot\\frac{db}{da}\\longrightarrow\\\\[0.3cm]\n2\\sqrt{2y+b}=-2\\sqrt{2x+a}\\cdot\\frac{db}{da}\\longrightarrow\\\\[0.3cm]\n\\boxed{\\sqrt{2y+b}=-\\sqrt{2x+a}\\cdot\\frac{db}{da}}"
Let
"b(a)=-\\frac{a}{\\lambda}+C\\longrightarrow\\frac{db}{da}=-\\frac{1}{\\lambda}"
Then,
"\\sqrt{2y+b}=-\\sqrt{2x+a}\\cdot\\frac{db}{da}\\longrightarrow\\\\[0.3cm]\n\\sqrt{2y+b}=\\frac{1}{\\lambda}\\sqrt{2x+a}\\longrightarrow\\\\[0.3cm]\n\\boxed{2y=\\frac{2x+a}{\\lambda^2}-b}\\\\[0.3cm]\n\\underbrace{\\sqrt{2x+a}+\\sqrt{2y+b}}_{z}=\\sqrt{2x+a}-\\sqrt{2x+a}\\cdot\\left(-\\frac{1}{\\lambda}\\right)\\\\[0.3cm]\nz=\\left(1+\\frac{1}{\\lambda}\\right)\\sqrt{2x+a}\\longrightarrow\\\\[0.3cm]\n\\boxed{z^2=\\left(\\frac{1+\\lambda}{\\lambda}\\right)^2(2x+a)}"
Consider the found function along with
"z^2=2(1+\\lambda^{-1})(x+y\\lambda)-\\mu\\longrightarrow\\\\[0.3cm]\n\\boxed{z^2=2\\left(\\frac{1+\\lambda}{\\lambda}\\right)(x+y\\lambda)-\\mu}"
Then,
"z^2=\\left(\\frac{1+\\lambda}{\\lambda}\\right)^2(2x+a)\\\\[0.3cm]\nz^2=2\\left(\\frac{1+\\lambda}{\\lambda}\\right)(x+y\\lambda)-\\mu\\\\[0.3cm]\n\\left(\\frac{1+\\lambda}{\\lambda}\\right)^2(2x+a)=2\\left(\\frac{1+\\lambda}{\\lambda}\\right)(x+y\\lambda)-\\mu\\\\[0.3cm]\n\\left(\\frac{1+\\lambda}{\\lambda}\\right)(2x+a)=2(x+y\\lambda)-\\frac{\\lambda}{1+\\lambda}\\cdot\\mu\\\\[0.3cm]\n(1+\\lambda)(2x+a)=2\\lambda(x+y\\lambda)-\\frac{\\lambda^2}{1+\\lambda}\\cdot\\mu\\\\[0.3cm]\n2x+a+2x\\lambda+a\\lambda=2x\\lambda+2y\\lambda^2-\\frac{\\lambda^2}{1+\\lambda}\\cdot\\mu\\\\[0.3cm]\na(1+\\lambda)=2y\\lambda^2-2x-\\frac{\\lambda^2}{1+\\lambda}\\cdot\\mu\\\\[0.3cm]\na(1+\\lambda)=\\left(\\frac{2x+a}{\\lambda^2}-b\\right)\\lambda^2-2x-\\frac{\\lambda^2}{1+\\lambda}\\cdot\\mu\\\\[0.3cm]\na(1+\\lambda)=2x+a-b\\lambda^2-2x-\\frac{\\lambda^2}{1+\\lambda}\\cdot\\mu\\\\[0.3cm]\nb\\lambda^2=-a\\lambda-\\frac{\\lambda^2}{1+\\lambda}\\cdot\\mu\\\\[0.3cm]\n\\boxed{b=-\\frac{a}{\\lambda}-\\frac{\\mu}{1+\\lambda}}"
Conclusion,
The complete integral (ii) is the envelope of one parameter sub-system obtained by taking
"b=-\\frac{a}{\\lambda}-\\frac{\\mu}{1+\\lambda}"
Comments
Leave a comment